Factors influencing creatine lading into human skeletal muscle - Snow, R. J. (Exercise and Sport Sciences Reviews, 2003)
This review describes several factors involved in regulating skeletal muscle creatine uptake and total creatine content. Skeletal muscle total creatine content increases with oral creatine supplementation, although the response is variable. Factors that may account for this variation are carbohydrate intake, physical activity, training status, and possibly fiber type.